(untitled) (Boca Raton, Fl., 2002)
This book provides a central resource and available reference for the analysis of well-known functional food components, such as carbohydrates, lipids, and vitamins, and a unique resource for descriptions of the analytical methodology for non-nutrition food ingredients.
Thực phẩm chức năng
Keywords: Functional foods; Analysis